Bringing the outdoors in: designing a mobile sensory garden for children with sensory integration disorders in elementary schools - Taylor, Morgan (Kansas State University, 2017)
The purpose of this research was to develop a mobile sensory garden to help children with Sensory Integration Disorders. Sensory Integration (SI) is how an individual processes sensory information. Issues with sensory integration can lead to behavioral disorders, which can cause difficulties with social-emotional skills, gross motor skills, fine motor skills, play skills, and self-help skills. The goal of the project was to develop a mobile sensory garden to help alleviate or reduce the negative aspects of Sensory Integration Disorders. The research involved qualitative research, projective design, and evaluative research on a mobile sensory cart that was used in an elementary school in Topeka, Kansas. Methods included: interviews, design/build, and observation. The current sensory room was inventoried in Williams Science & Fine Arts Elementary Magnet School in Topeka, Kansas, and the children who used were observed. The faculty at the school, including the principal, teachers whose students use the current sensory room, counselors, and other support faculty, were interviewed. Once the observations were analyzed, a mobile sensory garden cart was designed and built. The new cart was brought to the elementary school and placed in the sensory room. A second phase of observation assessed how the children interacted with the new mobile sensory garden cart. During the second phase of observation the children showed intense interest in the mobile sensory garden cart. Some of this can be attributed to it being a new item in the sensory room. Some of the most popular items included the zen garden, wood slices on the wooden dowel, and the plants. In the second week children transitioned to using both the sensory garden cart and the original items in the sensory room. When an item on the sensory garden cart best suited their needs, that item was chosen and when their needs were best suited by other items in the room then that item was chosen. Overall the mobile sensory garden cart was beneficial to the school and the children. It can be easily replicated and modified to fit the individual needs of the children and school.
Keywords: Sensory integration disorders; Sensory processing disorders; Sensory gardens; Horticulture therapy; Mobile cartSensory Integration